Global geochemical fingerprinting of plume intensity suggests coupling with the supercontinent cycle - Gamal EL Dien, Hamed; Doucet, Luc; Li, Zheng-Xiang; Cox, Grant; Mitchell, Ross (NATURE PUBLISHING GROUP, 2019)
Plate tectonics and mantle plumes are two of the most fundamental solid-Earth processes that have operated through much of Earth history. For the past 300 million years, mantle plumes are known to derive mostly from two large low shear velocity provinces (LLSVPs) above the core-mantle boundary, referred to as the African and Pacific superplumes, but their possible connection with plate tectonics is debated. Here, we demonstrate that transition elements (Ni, Cr, and Fe/Mn) in basaltic rocks can be used to trace plume-related magmatism through Earth history. Our analysis indicates the presence of a direct relationship between the intensity of plume magmatism and the supercontinent cycle, suggesting a possible dynamic coupling between supercontinent and superplume events. In addition, our analysis shows a consistent sudden drop in MgO, Ni and Cr at ~3.2–3.0 billion years ago, possibly indicating an abrupt change in mantle temperature at the start of global plate tectonics.